KELOMPOK AKTIVIS PARTAI POLITIK ISLAM SEBAGAI KOMUNIKATOR: Kajian kritis terhadap keberfungsian aktivis dalam kancah perpolitikan Indonesia - Yusri Yusri (Jurnal Komunikasi dan Media, 2024)
This article discusses Islamic political party activist groups as communicators. Because this discussion is related to Islamic political communication, political party activists are seen as communicators in Islamic communication. Because in Indonesia the majority of people are Muslims, as communicators of Islamic political parties, communicators should be oriented from an Islamic perspective. In reality, on the contrary, there are still Islamic political party communicators oriented towards other than Islamic communication. Therefore, this paper examines how prepared Islamic political party activists should be before communicating, while communicating and after communicating through the lens of Islamic communication. To answer all of this, this research uses a literature review with a qualitative approach. Researchers attempt to critically examine various literature related to the issue of political communicators and then describe it carefully. It can be described that Islamic political party activists as communicators still need to learn various things to perfect the competence of quality communicators in the eyes of their religion, state and party.